High biologically effective dose radiation therapy using brachytherapy in combination with external beam radiotherapy for high-risk prostate cancer - Okamoto, Keisei; Wada, Akinori; Kohno, Naoaki (Journal of Contemporary Brachytherapy, 2017)
Purpose : To evaluate the outcomes of high-risk prostate cancer patients treated with biologically effective dose (BED) ≥ 220 Gy of high-dose radiotherapy, using low-dose-rate (LDR) brachytherapy in combination with external beam radiotherapy (EBRT) and short-term androgen deprivation therapy (ADT). Material and methods : From 2005 to 2013, a total of 143 patients with high-risk prostate cancer were treated by radiotherapy of BED ≥ 220 Gy with a combination of LDR brachytherapy, EBRT, and androgen deprivation therapy (ADT). The high-risk patients in the present study included both high-risk and very high-risk prostate cancer. The number of high-risk features were: 60 patients with 1 high-risk factor (42%), 61 patients with 2 high-risk factors (43%), and 22 patients with 3 high-risk factors (15%) including five N1 disease. External beam radiotherapy fields included prostate and seminal vesicles only or whole pelvis depending on the extension of the disease. Biochemical failure was defined by the Phoenix definition. Results : Six patients developed biochemical failure, thus providing a 5-year actual biochemical failure-free survival (BFFS) rate of 95.2%. Biochemical failure was observed exclusively in cases with distant metastasis in the present study. All six patients with biochemical relapse had clinical failure due to bone metastasis, thus yielding a 5-year freedom from clinical failure (FFCF) rate of 93.0%. None of the cases with N1 disease experienced biochemical failure. We observed four deaths, including one death from prostate cancer, therefore yielding a cause-specific survival (CSS) rate of 97.2%, and an overall survival (OS) rate of 95.5%. Conclusions : High-dose (BED ≥ 220 Gy) radiotherapy by LDR in combination with EBRT has shown an excellent outcome on BFFS in high-risk and very high-risk cancer, although causal relationship between BED and BFFS remain to be explained further.